Aspirations of Rural Schooled Youth. Peasant Habitus and Conditions of Educability - Sepúlveda , Álvaro Andrés Rivera; Salazar, Omar Cabrales; Sánchez, Laura Fernanda Ramírez (Journal of Ecohumanism, 2025)
The aspirations of rural schooled young people are investigated from the perspective of the habitus of origin and the conditions of educability. A descriptive study with a mixed approach was designed with the participation of students, teachers, directors and parents of rural educational institutions in a Colombian province. The results show that the habitus of origin hastens many young people to establish aspirations that are not in accordance with the academic project established by the school, but also reveals a process of reordering of the habitus due to school discourses. The school’s interest in having more and more young people pursue higher education is truncated by the force of attraction of cultural and socio-familial capitals. Likewise, the aspirations of young people, in terms of rooting/uprooting, are strongly based on an objective impossibility: hopelessness in the face of the life opportunities offered by the countryside for small and medium producers. It is concluded that the rural school cannot strengthen the peasant habitus and achieve its educational purposes if, in the first place, the structural bases of exclusion and social injustice that the Colombian agricultural sector is going through are not modified.